2021
DOI: 10.1093/nar/gkab348
|View full text |Cite
|
Sign up to set email alerts
|

Genome editing in mammalian cells using the CRISPR type I-D nuclease

Abstract: Adoption of CRISPR–Cas systems, such as CRISPR–Cas9 and CRISPR–Cas12a, has revolutionized genome engineering in recent years; however, application of genome editing with CRISPR type I—the most abundant CRISPR system in bacteria—remains less developed. Type I systems, such as type I-E, and I-F, comprise the CRISPR-associated complex for antiviral defense (‘Cascade’: Cas5, Cas6, Cas7, Cas8 and the small subunit) and Cas3, which degrades the target DNA; in contrast, for the sub-type CRISPR–Cas type I-D, which lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 65 publications
2
31
0
Order By: Relevance
“…Classification of subtype has been more complicated (for details, please refer to a review by Makarova et al, 2020) . Recently, we identified that Cas10 is an important component in TiD ( Osakabe et al, 2020 , 2021 ). This diversification of CRISPR–Cas results from evolution in an intensive arms race between bacteria and their phage foes ( Hampton et al, 2020 ).…”
Section: Future Perspectivesmentioning
confidence: 99%
See 3 more Smart Citations
“…Classification of subtype has been more complicated (for details, please refer to a review by Makarova et al, 2020) . Recently, we identified that Cas10 is an important component in TiD ( Osakabe et al, 2020 , 2021 ). This diversification of CRISPR–Cas results from evolution in an intensive arms race between bacteria and their phage foes ( Hampton et al, 2020 ).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Recently, we characterized type I-D (TiD) CRISPR–Cas loci from Microcystis aeruginosa , and successfully developed a genome editing tool, which we named TiD, based on this system ( Osakabe et al, 2020 , 2021 ; Figure1A ; Figure 3B ). Several groups have reported in vitro DNA binding and cleavage capability of several type I-D systems from bacteria such as Sulfolobus islandicus and Synechocystis sp.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In type I-C systems, the Cas5 subunit possesses crRNA processing activity and Cas6 is absent (21). Although more complex than the streamlined class 2 systems such as Cas9 and Cas12, type I effectors have been utilised for a growing range of genome editing approaches and are particularly useful for long range genome edits (7,(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%